Transcriptome sequencing of hepatocellular carcinoma uncovers multiple types of dysregulated ncRNAs - Zhang, Li; Wang, Chunmei; Lu, Xiaojie; Xu, Xiao; Shi, Tieliu; Chen, Jinlian (Frontiers in Oncology, 2022)
Transcriptome profiling of hepatocellular carcinoma (HCC) by next generation sequencing technology (NGS) has been broadly performed by previous researches, which facilitate our understanding of the molecular mechanisms of HCC formation, progression and metastasis. However, few studies jointly analyze multi-types of noncoding RNAs (ncRNAs), including long noncoding RNAs (lncRNAs), circular RNAs (circRNAs) and micro-RNAs (miRNAs), and further uncover their implications in HCC. In this study, we observed that the circRNA cZRANB1 and lncRNA DUXAP10 were not only significantly up-regulated in tumor tissues, but also higher expressed in blood exosomes of HCC as compared with healthy donors. From the analysis of subclass-associated dysregulated ncRNAs, we observed DLX6-AS1, an antisense RNA of DLX6, and the sense gene DLX6 were highly expressed in S1, a subclass with a more invasive/disseminative phenotype. High correlation between DLX6-AS1 and DLX6 suggested DLX6-AS1 may function via promoting the transcription of DLX6. Integrative analysis uncovers circRNA-miRNA, lncRNA-miRNA and competing endogenous RNA networks (ceRNAs). Specifically, cZRANB1, LINC00501, CTD-2008L17.2, and SLC7A11-AS1 may function as ceRNAs that regulate mRNAs by competing the shared miRNAs. Further prognostic analysis demonstrated that the dysregulated ncRNAs had the potential to predict HCC patient’s overall survival. In summary, we identified some novel circRNAs and miRNAs, and dysregulated ncRNAs that could participate in HCC tumorigenesis and progression by inducing transcription of their neighboring genes, increasing their derived miRNAs, or acting as miRNA sponges. Moreover, our systematic analysis provides not only rich data resources for related researchers, but also new insights into the molecular basis of how different ncRNAs coordinately or antagonistically participate into the pathogenesis process of diseases.